2021
DOI: 10.1101/2021.09.07.459259
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motivations, concerns and selection biases when posting preprints: a survey of bioRxiv authors

Abstract: Since 2013, the usage of preprints as a means of sharing research in biology has rapidly grown, in particular via the preprint server bioRxiv. Recent studies have found that journal articles that were previously posted to bioRxiv received a higher number of citations or mentions/shares on other online platforms compared to articles in the same journals that were not posted. However, the exact causal mechanism for this effect has not been established, and may in part be related to authors' biases in the selecti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…This result aligns well with previous studies. Fraser, Mayr & Peters (2021) conducted a survey of authors of bioRxiv preprints and found that for more than 85% of survey participants the main motivations for preprinting their work were to share their findings more quickly and to increase awareness of their research. In a survey conducted by ASAPbio (2020) , more than two thirds of 500 surveyed preprint authors and non-authors mentioned “increasing the speed of research communication” and “preprints are free to read” as the main benefits of preprints.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result aligns well with previous studies. Fraser, Mayr & Peters (2021) conducted a survey of authors of bioRxiv preprints and found that for more than 85% of survey participants the main motivations for preprinting their work were to share their findings more quickly and to increase awareness of their research. In a survey conducted by ASAPbio (2020) , more than two thirds of 500 surveyed preprint authors and non-authors mentioned “increasing the speed of research communication” and “preprints are free to read” as the main benefits of preprints.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing adoption of preprinting has raised questions regarding the motivations of authors who choose to engage in preprinting. Multiple studies have surveyed or interviewed preprint authors, research funding representatives, research-conducting organisations, and other stakeholders ( ASAPbio, 2020 ; Chiarelli et al, 2019 ; Fraser, Mayr & Peters, 2021 ). These studies consistently identified the rapid dissemination of research outputs as the primary motivation for preprint adoption among participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, despite many respondents distrusting preprints due to lack of peer review, many were divided on if peer review should become part of the preprint process. This may be because preprints allow for the rapid dissemination of research as there is a delay from journal submission to publication when undergoing peer review 2,6 . If peer review were to be incorporated into preprinting in the same way it is done for journals, then the work of peer reviewers would increase, and the delay would become much longer.…”
Section: Opinions On the Benefits And Consequences Of Preprintsmentioning
confidence: 99%
“…In addition, compared with more established researchers, early-career researchers place more value on the opportunities preprints provide for receiving feedback and raising awareness about their research. 7 Because research outputs are free to post and read, preprints offer a more affordable way for early-career researchers, who are less likely to have funds to cover article processing charges, to participate in open science. In addition, preprints are freely accessible, providing for wider and fairer reach.…”
Section: What Are Preprints and Why Do Scholars Use Them?mentioning
confidence: 99%